REVOCATION OF BUSINESS COMPETITION SUPERVISORY COMMISSION DECISIONS OVER CARTEL-RELATED CASES IN INDONESIA - Herwastoeti (Audito Comparative Law Journal (ACLJ), 2021)
Business Competition Supervisory Commission (henceforth KPPU), a law enforcement body in Indonesia, was established based on Antimonopoly Law. This commission is a quasi-judicial body holding executorial authority over business competition-related cases. The crucial issue is apparent when business people submit petitions to the District Court since, from this point, different approaches and treatments between the KPPU and the District Court are revealed. This weak legal procedure, especially regarding the efforts made for petitions, is often seen as an opportunity by business people to stand against the decisions of the KPPU by submitting petitions to District Court, and several cartel-related cases have been reinforced by Supreme Court. This research employed normative-juridical methods involving secondary data that were further analyzed by emphasizing juridical aspects for the analysis of the qualitative analysis method to present a description, from which a conclusion and recommendations were drawn. With it, decisions of the KPPU would not be labeled weak in law enforcement concerning business competition. Moreover, this approach is intended to deter business people regarding the violations of Law concerning Antimonopoly especially those regarding cartels which not only harm business people, but also the members of public in general.